Sodium-ion battery negative electrode material and preparation method and application thereof

By combining two active materials such as antimony sulfide and molybdenum selenide, and using nanostructure design and carbon material composite method, a sodium ion battery negative electrode material Sb2S3/MoSe2/C with a multi-stage layered rod structure was prepared, which solved the shortcomings of the existing electrode materials in terms of cycle performance and rate performance, and significantly improved the electrochemical performance of sodium ion battery.

CN119650630APending Publication Date: 2025-03-18HUACAI (HEFEI) NEW ENERGY TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411752443.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-02
Publication Date
2025-03-18

AI Technical Summary

Technical Problem

There is still room for improvement in the circulation and rate performance of existing sodium ion battery electrode materials, especially in terms of synergistic optimization between heterostructure and electrochemical properties.

Method used

By combining two active materials such as antimony sulfide (Sb2S3) and molybdenum selenide (MoSe2), the sodium ion battery negative electrode material Sb2S3/MoSe2/C with a multi-stage layered rod-like structure was prepared.

Benefits of technology

This material significantly improves the cycling and rate performance of sodium ion batteries, provides a shorter ion diffusion path, a larger specific surface area and a more stable structural framework, extending the battery's service life and improving the overall performance of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119650630A_ABST
    Figure CN119650630A_ABST
Patent Text Reader

Abstract

The invention discloses a sodium ion battery negative electrode material as well as a preparation method and application thereof. The preparation method comprises the following steps: S1, preparing a Sb2S3 nanorod; and S2, uniformly dispersing the Sb2S3 nanorod in an aqueous dispersion of a carbon source, adding molybdate into the aqueous dispersion, then slowly adding a selenium-containing solution into the aqueous dispersion, carrying out a hydrothermal reaction, and calcining to prepare the sodium-ion battery negative electrode material with the composition of Sb2S3 / MoSe2 / C. The invention also discloses a preparation method of the sodium-ion battery negative electrode material with the composition of Sb2S3 / MoSe2 / C. The Sb2S3 nanorod is taken as a precursor or a template, the Sb2S3 / MoSe2 heterostructure material with a unique multi-stage layered rod-shaped structure is prepared by adopting methods such as nanostructure design, carbon material compounding and heterostructure construction, and the Sb2S3 / MoSe2 heterostructure material has excellent cycle performance and rate capability as a sodium-ion battery negative electrode material; the development of the sodium ion battery can be further promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the field of sodium ion batteries, and in particular relates to a sodium ion battery negative electrode material and a preparation method and application thereof. Background Art

[0002] Sodium-ion batteries have many advantages over traditional lithium-ion batteries: (1) Cost: Sodium resources are abundant and low in cost; (2) Safety: Sodium ions are larger in size, have a lower risk of thermal runaway, and are more stable, which can reduce battery damage and safety risks; (3) Environmental adaptability: Sodium-ion batteries perform well under extreme temperatures. Overall, the theoretical material cost of sodium-ion batteries is 30%-40% lower than that of lithium-ion batteries, making them potential alternatives in large-scale energy storage, low-speed electric vehicles and other fields.

[0003] At present, in-depth research and innovation are still needed in electrode materials, electrolyte systems and battery structures to achieve higher performance and more reliable sodium-ion batteries. One of the research focuses of sodium-ion batteries is the research and development of electrode materials, which need to have high ion conductivity, excellent electrochemical properties and good structural stability.

[0004] Electrode materials with heterostructures can effectively improve the kinetic performance of sodium-ion batteries and accelerate ion / electron diffusion, etc., to improve the electrochemical performance of sodium-ion batteries, and have become one of the research hotspots of sodium-ion battery electrode materials. Different interface interactions in heterostructures may affect electrochemical processes such as charge transfer and ion diffusion. Therefore, it is still necessary to continuously research and develop electrode materials with different heterostructures to achieve further improvement in the electrochemical performance of sodium-ion batteries. Summary of the invention

[0005] In view of this, the primary purpose of the present invention is to provide a sodium ion battery negative electrode material based on two active materials, antimony sulfide (Sb2S3) and molybdenum selenide (MoSe2), through nanostructure design, carbon material composite and heterostructure construction, to obtain a high-performance sodium ion battery negative electrode material, the sodium ion battery negative electrode material has excellent cycle performance and rate performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] The first aspect of the present invention provides a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:

[0008] S1, preparation of Sb2S3 nanorods;

[0009] S2. The Sb2S3 nanorods are uniformly dispersed in an aqueous dispersion of a carbon source, and molybdate is added thereto, and then a selenium-containing solution is slowly added thereto. After a hydrothermal reaction, the solution is calcined to obtain a sodium ion battery negative electrode material having a composition of Sb2S3 / MoSe2 / C.

[0010] The preparation method of the present invention can be used to prepare a sodium ion battery negative electrode material with a composition of Sb2S3 / MoSe2 / C, which has a high-quality Sb2S3 / MoSe2 heterogeneous structure. Specifically, it has a special microstructure, a multi-level hierarchical rod-like structure, and has excellent structural dimensions. This unique multi-level hierarchical structure and size are directly related to the electrochemical properties of the material, providing a shorter ion diffusion path, a larger specific surface area or a more stable structural framework, giving the sodium ion battery negative electrode material more excellent electrochemical properties, and can improve the cycle performance and rate performance of the sodium ion battery.

[0011] The second aspect of the present invention provides a sodium ion battery negative electrode material, which is prepared by the preparation method described above.

[0012] The microstructure of the negative electrode material for the sodium ion battery is a multi-level layered rod-like structure with a length of 3 to 6 μm and a width of 50 to 100 nm.

[0013] The third aspect of the present invention provides a sodium ion battery negative electrode sheet, which contains the sodium ion battery negative electrode material prepared by the preparation method described above or the sodium ion battery negative electrode material described above.

[0014] A fourth aspect of the present invention provides a sodium ion battery comprising the sodium ion battery negative electrode sheet described above.

[0015] Beneficial effects of the present invention:

[0016] In the present invention, a high-quality Sb2S3 / MoSe2 heterostructure is successfully prepared using Sb2S3 nanorods as a precursor. After MoSe2 and Sb2S3 form a heterostructure, the advantages of the two can complement each other and produce a synergistic effect. Specifically, the layered structure of MoSe2 is conducive to the diffusion of sodium ions; Sb2S3 can provide additional sodium storage sites, thereby increasing the overall sodium storage capacity of the material; and when Sb2S3 changes in volume, MoSe2 can play a supporting and buffering role, inhibiting the pulverization and structural damage of the material, maintaining the integrity of the electrode structure, thereby significantly improving the cycle stability and extending the service life of the battery. At the same time, the formation of the heterostructure in the present invention can improve the electron conduction path, improve the conductivity of the material, and thus improve the rate performance of the battery.

[0017] In addition, in the present invention, a carbon source is introduced in the preparation of the heterostructure. The introduced carbon source can not only increase the conductivity of the material, but also can regulate the growth direction, morphology or crystallinity of the heterostructure, which has an outstanding contribution to the formation of the heterostructure with a specific microstructure in the present invention.

[0018] The Sb2S3 / MoSe2 / C sodium ion battery negative electrode material prepared by the preparation method of the present invention has a unique microstructure (a multi-level layered rod-like structure) and a precisely controlled structural size, which provides a shorter ion diffusion path, a larger specific surface area or a more stable structural framework, so that the prepared sodium ion battery negative electrode material has better cycle performance and rate performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the XRD spectrum of the Sb2S3 nanorods prepared in Example 1.

[0020] Figure 2 This is the XRD spectrum of the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C prepared in Example 1.

[0021] Figure 3 The following are scanning electron microscope photographs (SEM) of the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C prepared in Example 1 at different magnifications.

[0022] Figure 4 The low current cycle curves of button cells assembled from the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C prepared in Example 1 and the negative electrode materials Sb2S3 / C and MoSe2 / C prepared in Comparative Example 1 and Comparative Example 2.

[0023] Figure 5 This is a high current and long cycle performance diagram of the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C obtained in Example 1.

[0024] Figure 6 The rate performance curve of the button cell assembled with the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C prepared in Example 1 and the negative electrode materials Sb2S3 / C and MoSe2 / C prepared in Comparative Example 1 and Comparative Example 2. DETAILED DESCRIPTION

[0025] Embodiments of the present invention are described in detail below. The embodiments described below are exemplary and are only used to explain the present invention, and should not be construed as limiting the present invention.

[0026] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.

[0027] The first aspect of the present invention discloses a method for preparing a negative electrode material for a sodium ion battery, comprising the following steps:

[0028] S1, preparation of Sb2S3 nanorods;

[0029] S2. The Sb2S3 nanorods are uniformly dispersed in an aqueous dispersion of a carbon source, and molybdate is added thereto, and then a selenium-containing solution is slowly added thereto. After a hydrothermal reaction, the solution is calcined to obtain a sodium ion battery negative electrode material having a composition of Sb2S3 / MoSe2 / C.

[0030] In the present invention, Sb2S3 nanorods are used as precursors, and a high-performance sodium ion battery negative electrode material Sb2S3 / MoSe2 / C is prepared through a variety of methods such as nanostructure design, carbon material composite and heterostructure construction. The sodium ion battery negative electrode material has excellent cycle performance and rate performance.

[0031] In the present invention, in step S1, the preparation of the Sb2S3 nanorods comprises the following steps:

[0032] S11, add SbCl3 to deionized water, stir evenly, then add Na2S·9H2O and ethylene glycol respectively, stir evenly, to obtain a precursor solution;

[0033] S12, subjecting the precursor solution to a hydrothermal reaction to obtain Sb2S3 nanorods.

[0034] Wherein, in the precursor solution, the molar ratio of SbCl3 and Na2S·9H2O is (1-2): (1.5-3);

[0035] and / or, the volume ratio of the amount of SbCl3 to deionized water (1 mmol to 4 mmol): (30 mL to 50 mL);

[0036] And / or, the volume ratio of ethylene glycol to deionized water is 1:1.

[0037] Wherein, the temperature of the hydrothermal reaction is 150°C to 200°C, and the time is 10h to 15h.

[0038] It is understood that in step S2, after the hydrothermal reaction, the hydrothermal reaction is further included in the steps of washing, centrifuging and drying, which is a relatively conventional operation in the art without special restrictions. In some specific embodiments of the present invention, the washing is first washed with deionized water for 2 to 4 times, and then washed with anhydrous ethanol for 1 to 3 times. The speed of the centrifugation is 7500 to 9000 r / min, and the centrifugation time is 10 to 15 min. The drying temperature is 55 to 65 ° C.

[0039] In the present invention, the carbon source is an organic carbon source or an inorganic carbon source commonly used in the art for preparing negative electrode materials. Specific examples include at least one of glucose, sucrose, cellulose, dopamine, and graphene, but are not limited thereto. In some specific embodiments of the present invention, the carbon source is glucose.

[0040] Furthermore, the concentration of the aqueous dispersion of a specific carbon source can be determined by known methods or experiments according to experimental requirements such as material properties. In some specific embodiments of the present invention, the concentration of the carbon source in the aqueous dispersion of the carbon source is 0.03 to 0.08 M, for example, it can be any concentration of 0.03 M, 0.04 M, 0.05 M, 0.06 M, 0.07 M, or 0.08 M.

[0041] In the present invention, the introduction of a carbon source, on the one hand, increases the conductivity of the material, and on the other hand, can regulate the growth direction, morphology or crystallinity of the heterostructure, providing important support for obtaining a unique heterostructure microstructure.

[0042] Further, the volume ratio of the amount of the Sb2S3 nanorods to the aqueous dispersion of the carbon source (1mmol to 2mmol): (30mL to 50mL);

[0043] And / or, the dispersion time of the Sb2S3 nanorods in the aqueous dispersion of the carbon source is 20 to 40 minutes to achieve sufficient and uniform mixing of the Sb2S3 nanorods and the carbon source.

[0044] In the present invention, the molybdate is sodium molybdate or ammonium molybdate. For example, in a specific embodiment, the molybdate raw material used is Na2MoO4·2H2O or (NH4)6Mo7O 24 ·4H2O; wherein the molybdate and Sb2S3 nanorods are prepared according to a molar ratio of Mo to Sb of 1:2.

[0045] In the present invention, the selenium-containing solution is formed by dissolving selenium powder in hydrazine hydrate, wherein the volume ratio of the amount of the selenium powder to the hydrazine hydrate is (2mmol-5mmol): (5mL-10mL); at the same time, in order to ensure the progress of subsequent reactions, the selenium powder needs to be fully stirred when added to the hydrazine hydrate. In some specific embodiments of the present invention, the stirring speed of the selenium powder in the hydrazine hydrate is 200r / min-500r / min, and the time is 2-4h.

[0046] In the present invention, hydrazine hydrate is used as a reducing agent to perform a pretreatment step on Se powder, and in the subsequent reaction, hydrazine hydrate is used as a coordinating agent to perform surface modification on Sb2S3 or MoSe2 precursors. Specifically, the nitrogen atom and lone pair electrons in the hydrazine hydrate molecule can react with metal ions (such as Sb 3+ 、Mo 4+ The coordination bonds formed by the metal ions make the metal ions more stable in the solution. This coordination effect can control the release rate of the metal ions and avoid their precipitation or agglomeration too quickly in the early stage of the reaction, which is conducive to the formation of uniformly dispersed reaction precursors and lays the foundation for the subsequent generation of high-quality heterostructures, thereby promoting the formation of heterostructures and improving the performance of heterostructures.

[0047] Furthermore, in the present invention, in step S2, the temperature of the hydrothermal reaction is 180°C to 210°C, and the time is 22h to 24h. By setting the hydrothermal conditions, the two active materials are promoted to achieve uniform mixing and combination at the atomic or molecular level to form an ideal heterogeneous structure.

[0048] It can be understood that after the hydrothermal reaction in step S2, the steps of washing, centrifuging and drying the product of the hydrothermal reaction are also included. These are well-known means in the art and are not particularly limited. In some specific embodiments of the present invention, the washing is first washed with water 2 to 4 times, and then washed with anhydrous ethanol 1 to 3 times; the centrifugal speed is 7500 to 9000 r / min, and the centrifugal time is 10 to 15 min; the drying temperature is 60°C.

[0049] In the present invention, the calcination is carried out in a protective atmosphere, the calcination temperature is 400-500° C., and the calcination time is 3-5 hours.

[0050] The protective atmosphere used is a gas that is inert to the reaction materials and can isolate oxygen, which is well known in the art. For example, it can be nitrogen or one of the rare gases (such as helium and argon). In some specific embodiments of the present invention, the flow rate of the protective gas is 50-100 mL / min; the heating rate of the calcination is 5°C / min, but it is not limited to this and can be adjusted or optimized according to specific needs.

[0051] The second aspect of the present invention discloses a sodium ion battery negative electrode material, which is prepared by the preparation method described above, and the sodium ion battery negative electrode material has a unique microstructure shape and size. Specifically, the microstructure of the sodium ion battery negative electrode material is a multi-level hierarchical rod-like structure with a length of 3 to 6 μm and a width of 50 to 100 nm. This multi-level hierarchical rod-like structure and size are directly related to the electrochemical properties of the material, providing a shorter ion diffusion path, a larger specific surface area and a more stable structural framework. At the same time, the material has a higher conductivity, and the conversion reaction mechanism of MoSe2 and the synergistic effect of the multi-step alloying reaction of Sb2S3, as well as the introduction of a carbon source, give the material excellent cycle performance and rate performance.

[0052] The electrochemical reaction process of the negative electrode material of the sodium ion battery in the present invention is as follows:

[0053] (1) Discharge process

[0054] MoSe2+xNa++xe - →Na x MoSe2;

[0055] Sb2S3+6Na + +6e - →2Sb+3Na2S;

[0056] Sb+3Na++3e - →Na3Sb;

[0057] Na x MoSe2+(4-x)Na + +(4-x)e - →Mo+2Na2Se.

[0058] (2) Charging process

[0059] Na3Sb→Sb+3Na + +3e - ;

[0060] 2Sb+3Na2S→Sb2S3+6Na + +6e - ;

[0061] Mo+2Na2Se→Na x MoSe2+(4-x)Na + +(4-x)e - ;

[0062] Na x MoSe2→MoSe2+xNa + +xe - .

[0063] The third aspect of the present invention discloses a sodium ion battery negative electrode sheet, which contains the sodium ion battery negative electrode material prepared by the preparation method described above or the sodium ion battery negative electrode material described above.

[0064] It is understandable that the preparation and composition of the negative electrode sheet can be carried out by conventional methods in the art without special restrictions. The active material of the negative electrode sheet also includes a conductive agent, etc., which can be of types well known in the art.

[0065] The fourth aspect of the present invention discloses a sodium ion battery, comprising the sodium ion battery negative electrode sheet described above.

[0066] It is understandable that the sodium ion battery also includes key materials such as the positive electrode, electrolyte and separator, all of which can be of the types conventionally used in the art without special limitation.

[0067] The sodium ion battery negative electrode sheet and the sodium ion battery described in the present invention have the same advantages or effects as the sodium ion battery negative electrode material described above, so they are not described in detail here.

[0068] The present invention is described below by means of specific examples. It should be noted that the following specific examples are only for illustrative purposes and do not limit the scope of the present invention in any way. In addition, unless otherwise specified, methods without specific conditions or steps are conventional methods, and the reagents and materials used can be obtained from commercial channels.

[0069] Example 1

[0070] This embodiment provides a method for preparing a sodium ion battery negative electrode material Sb2S3 / MoSe2 / C, and the specific steps are as follows:

[0071] (1) Add 0.913 g of SbCl3 to 50 mL of deionized water and stir for 30 min. Then weigh 1.938 g of Na2S·9H2O and add it. Finally, add 50 mL of ethylene glycol and stir for 3 h.

[0072] (2) After the stirring is completed, the mixture is added into a 100 mL polytetrafluoroethylene reactor and subjected to solvent thermal reaction at 180° C. for 12 h to obtain a reaction product.

[0073] (3) The reaction product in step (2) was first washed three times with deionized water, then washed twice with anhydrous ethanol, and then centrifuged at a speed of 7500 r / min for 15 min, and finally dried at 60° C. to obtain Sb2S3 nanorods.

[0074] (4) Dissolve 100 mg of selenium powder in 8 mL of hydrazine hydrate and stir at 300 r / min for 2 h to form a hydrazine hydrate-selenium dark red-brown solution.

[0075] (5) Disperse 215 mg of Sb2S3 nanorods in 25 mL of 0.05 M glucose aqueous solution and perform ultrasonic dispersion for 30 min. Then add 160 mg of sodium molybdate and stir evenly.

[0076] (6) The mixed solution obtained in step (5) was slowly added to the dark red-brown solution of hydrazine hydrate-selenium in step (4), and then transferred to a 50 mL reactor and kept at 180° C. for 24 h.

[0077] (7) After cooling, the reaction product was washed three times with deionized water and twice with anhydrous ethanol, and then centrifuged at 8000 r / min for 15 min and dried at 60 °C for 12 h.

[0078] (8) The dried product was calcined at 600°C in an argon atmosphere for 2 h, wherein the argon flow rate was 80 mL / min and the heating rate was 5°C / min, to obtain the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C.

[0079] Example 2

[0080] This embodiment provides another method for preparing Sb2S3 / MoSe2 / C, a negative electrode material for a sodium ion battery, and the specific steps are as follows:

[0081] (1) Add 1.826 g of SbCl3 to 50 mL of deionized water and stir for 30 min. Then weigh 3.876 g of Na2S·9H2O and add it. Finally, add 50 mL of ethylene glycol and stir for 3 h.

[0082] (2) After the stirring is completed, the mixture is added into a 100 mL polytetrafluoroethylene reactor and subjected to solvent thermal reaction at 150° C. for 15 h to obtain a reaction product.

[0083] (3) The reaction product in step (2) was first washed three times with deionized water, then washed twice with anhydrous ethanol, and then centrifuged at a speed of 7500 r / min for 15 min, and finally dried at 60° C. to obtain Sb2S3 nanorods.

[0084] (4) Dissolve 100 mg of selenium powder in 5 mL of hydrazine hydrate and stir at 300 r / min for 2 h to form a hydrazine hydrate-selenium dark red-brown solution.

[0085] (5) Disperse 215 mg of Sb2S3 nanorods in 25 mL of 0.03 M sucrose aqueous solution and perform ultrasonic dispersion for 30 min. Then add 160 mg of sodium molybdate and stir evenly.

[0086] (6) The mixed solution obtained in step (5) was slowly added to the dark red-brown solution of hydrazine hydrate-selenium in step (4), and then transferred to a 50 mL reactor and kept at 200° C. for reaction for 23 h.

[0087] (7) After cooling, the reaction product was washed three times with deionized water and twice with anhydrous ethanol, and then centrifuged at 8000 r / min for 15 min and dried at 60 °C for 12 h.

[0088] (8) The dried product was calcined at 400°C in an argon atmosphere for 5 h, wherein the argon flow rate was 80 mL / min and the heating rate was 5°C / min, to obtain the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C.

[0089] Example 3

[0090] This embodiment provides another method for preparing Sb2S3 / MoSe2 / C, a negative electrode material for sodium ion batteries, and the specific steps are as follows:

[0091] (1) Add 0.913 g of SbCl3 to 50 mL of deionized water and stir for 30 min. Then weigh 1.938 g of Na2S·9H2O and add it. Finally, add 50 mL of ethylene glycol and stir for 3 h.

[0092] (2) After the stirring is completed, the mixture is added into a 100 mL polytetrafluoroethylene reactor and subjected to solvent thermal reaction at 200° C. for 10 h to obtain a reaction product.

[0093] (3) The reaction product in step (2) was first washed three times with deionized water, then washed twice with anhydrous ethanol, and then centrifuged at a speed of 7500 r / min for 15 min, and finally dried at 60° C. to obtain Sb2S3 nanorods.

[0094] (4) Dissolve 200 mg of selenium powder in 8 mL of hydrazine hydrate and stir at 300 r / min for 2 h to form a hydrazine hydrate-selenium dark red-brown solution.

[0095] (5) 430 mg of Sb2S3 nanorods were dispersed in 25 mL of 0.08 M glucose aqueous solution and ultrasonically dispersed for 30 min. Then, 223.5 mg of ammonium heptamolybdate tetrahydrate was added and stirred evenly.

[0096] (6) The mixed solution obtained in step (5) was slowly added to the dark red-brown solution of hydrazine hydrate-selenium in step (4), and then transferred to a 50 mL reactor and kept at 210° C. for 22 h.

[0097] (7) After cooling, the reaction product was washed three times with deionized water and twice with anhydrous ethanol, and then centrifuged at 8000 r / min for 15 min and dried at 60 °C for 12 h.

[0098] (8) The dried product was calcined at 500°C in an argon atmosphere for 3 h, wherein the argon flow rate was 80 mL / min and the heating rate was 5°C / min, to obtain the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C.

[0099] Comparative Example 1

[0100] This comparative example adopts the same implementation as Example 1, with the only difference being that the MoSe2 in the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C in Example 1 is replaced with an equal mass of Sb2S3.

[0101] That is, the negative electrode material of the sodium ion battery prepared in this comparative example is Sb2S3 / C. Other steps and process conditions are the same as those in Example 1.

[0102] Comparative Example 2

[0103] This comparative example adopts the same implementation as Example 1, with the only difference being that the Sb2S3 in the sodium ion battery negative electrode material Sb2S3 / MoSe2 / C in Example 1 is replaced with an equal mass of MoSe2.

[0104] That is, the negative electrode material of the sodium ion battery prepared in this comparative example is MoSe2 / C. Other steps and process conditions are the same as those in Example 1.

[0105] Material Characterization and Performance Testing

[0106] 1. Material Characterization

[0107] (1) XRD was used to characterize the Sb2S3 nanorods and Sb2S3 / MoSe2 / C materials prepared in Example 1. The results are as follows: Figure 1 and Figure 2 As shown in the figure, it can be seen that the measured diffraction peaks have a good correspondence with the PDF card library. 3 / In the MoSe2 / C spectrum, not only the characteristic peaks of Sb2S3 but also the characteristic peaks of MoSe2 can be seen, which confirms that the material prepared in Example 1 is composed of Sb2S3 and MoSe2.

[0108] (2) Figure 3 The SEM spectrum of the Sb2S3 / MoSe2 / C material in Example 1 is shown. It can be seen that the sample presents a rod-like structure with relatively uniform thickness and regular shape, and its surface is smoother. The rods are well separated without agglomeration, and their length is about 4μm to 6μm.

[0109] 2. Performance Testing

[0110] The sodium ion battery negative electrode materials prepared in the examples and comparative examples were assembled into button batteries according to the following method:

[0111] Negative electrode sheet: 140 mg of the sodium ion battery negative electrode material in the embodiment or comparative example is taken as the negative electrode active material, 30 mg of conductive carbon black (SP) is taken as the conductive agent, and 30 mg of carboxymethyl cellulose (CMC) is taken as the binder, mixed evenly and ground for 20 min, and then the mixture is transferred to an 8 mL glass bottle with a rotor, and then an appropriate amount of deionized water is added dropwise, and stirred for 10 h until the mixed slurry has a metallic luster; the prepared mixed slurry is coated on the surface of a 7 cm × 8 cm copper foil, and the loading amount of the active material on the copper foil is 1.0 mg cm -2 , dried at 60°C in vacuum for 12 h, and then taken out and punched into a negative electrode sheet with a diameter of 8 mm.

[0112] Using a metal sodium sheet with a diameter of 12.4 mm as the counter electrode and reference electrode and sodium perchlorate as the electrolyte, a button cell was assembled in a glove box with a water and oxygen content of less than 0.01 ppm.

[0113] The above button cell was tested for room temperature cycle performance and rate performance using a Blue Electric charge and discharge tester between 0.1 and 3V. Figures 4 to 6 .

[0114] pass Figure 4 It can be seen that at a current density of 0.2 A g -1 When the Sb2S3 / MoSe2 / C in Example 1 was cycled 100 times, the capacity remained at 436.5 mAh·g -1 The effect is significant due to the negative electrode materials in Comparative Examples 1 and 2. -1 At a high current density of 2.5 mAh·g, the Sb2S3 / MoSe2 / C in Example 1 maintained at 257.3 mAh·g after 450 cycles. -1 ( Figure 5 ), showing excellent cycle performance.

[0115] In addition, through Figure 6 It can be seen that Sb2S3 / MoSe2 / C in Example 1 has excellent rate performance and is superior to the negative electrode materials in Comparative Examples 1 and 2.

[0116] Based on the test results of the above embodiments and comparative examples, it can be concluded that the Sb2S3 / MoSe2 / C with Sb2S3 / MoSe2 heterostructure prepared in the present invention has excellent cycle performance and rate performance as a negative electrode material for sodium ion batteries.

[0117] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.

[0118] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A method for preparing a negative electrode material for a sodium ion battery, characterized in that: The following steps are involved: S1, preparation of Sb2S3 nanorods; S2. The Sb2S3 nanorods are uniformly dispersed in an aqueous dispersion of a carbon source, and molybdate is added thereto, and then a selenium-containing solution is slowly added thereto. After a hydrothermal reaction, the solution is calcined to obtain a sodium ion battery negative electrode material having a composition of Sb2S3 / MoSe2 / C.

2. The preparation method according to claim 1, characterized in that In step S1, the preparation of the Sb2S3 nanorods comprises the following steps: S11, add SbCl3 to deionized water, stir evenly, then add Na2S·9H2O and ethylene glycol respectively, stir evenly, to obtain a precursor solution; S12, subjecting the precursor solution to a hydrothermal reaction to obtain Sb2S3 nanorods; Preferably, in the precursor solution, the molar ratio of SbCl3 to Na2S·9H2O is (1-2): (1.5-3); and / or, the volume ratio of the amount of SbCl3 to deionized water (1 mmol to 4 mmol): (30 mL to 50 mL); and / or, the volume ratio of ethylene glycol to deionized water is 1:1; Preferably, the temperature of the hydrothermal reaction is 150° C. to 200° C., and the time is 10 h to 15 h.

3. The preparation method according to claim 1, characterized in that: The carbon source is an organic carbon source or an inorganic carbon source; Preferably, the carbon source is at least one of glucose, sucrose, cellulose, dopamine, and graphene; Preferably, the carbon source is glucose.

4. The preparation method according to claim 1, characterized in that: In the aqueous dispersion of the carbon source, the concentration of the carbon source is 0.03 to 0.08 M; and / or, the volume ratio of the amount of the Sb2S3 nanorods to the aqueous dispersion of the carbon source (1 mmol to 2 mmol): (30 mL to 50 mL); And / or, the dispersion time of the Sb2S3 nanorods in the aqueous dispersion of the carbon source is 20 to 40 minutes.

5. The preparation method according to claim 1, characterized in that: The molybdate is sodium molybdate or ammonium molybdate; Preferably, the molybdate and Sb2S3 nanorods are prepared according to a molar ratio of Mo to Sb of 1:

2.

6. The preparation method according to claim 1, characterized in that: The selenium-containing solution is formed by dissolving selenium powder in hydrazine hydrate; Preferably, the volume ratio of the amount of the selenium powder to hydrazine hydrate is (2mmol-5mmol): (5mL-10mL); Preferably, the stirring speed of the selenium powder in hydrazine hydrate is 200 r / min to 500 r / min, and the time is 2 to 4 hours.

7. The preparation method according to claim 1, characterized in that: In step S2, the temperature of the hydrothermal reaction is 180°C to 210°C, and the time is 22h to 24h; And / or, the calcination is carried out in a protective atmosphere, the calcination temperature is 400-500° C., and the calcination time is 3-5 hours; Preferably, the protective atmosphere is one of nitrogen or a rare gas, and the flow rate of the protective gas is 50 to 100 mL / min; Preferably, the heating rate of the calcination is 5°C / min.

8. A sodium ion battery negative electrode material, characterized in that: Prepared by the preparation method according to any one of claims 1 to 7; Preferably, the microstructure of the negative electrode material for a sodium ion battery is a multi-level layered rod-like structure with a length of 3 to 6 μm and a width of 50 to 100 nm.

9. A sodium ion battery negative electrode sheet, characterized in that: Contains a sodium ion battery negative electrode material prepared by the preparation method according to any one of claims 1 to 7 or a sodium ion battery negative electrode material according to claim 8.

10. A sodium ion battery, characterized in that: A sodium ion battery negative electrode sheet comprising the sodium ion battery negative electrode sheet according to claim 9.